PACAP27 mitigates an age‐dependent hippocampal vulnerability to PGJ2‐induced spatial learning deficits and neuroinflammation in mice - Avila, Jorge A. (Brain Behav, 2019)
BACKGROUND: Inflammation in the brain is mediated by the cyclooxygenase pathway, which leads to the production of prostaglandins. Prostaglandin (PG) D2, the most abundant PG in the brain, increases under pathological conditions and is spontaneously metabolized to PGJ2. PGJ2 is highly neurotoxic, with the potential to transition neuroinflammation into a chronic state and contribute to neurodegeneration as seen in many neurological diseases. Conversely, PACAP27 is a lipophilic peptide that raises intracellular cAMP and is an anti‐inflammatory agent. The aim of our study was to investigate the therapeutic potential of PACAP27 to counter the behavioral and neurotoxic effects of PGJ2 observed in aged subjects. METHODS: PGJ2 was injected bilaterally into the hippocampal CA1 region of 53‐week‐old and 12‐week‐old C57BL/6N male mice, once per week over 3 weeks (three total infusions) and included co‐infusions of PACAP27 within respective treatment groups. Our behavioral assessments looked at spatial learning and memory performance on the 8‐arm radial maze, followed by histological analyses of fixed hippocampal tissue using Fluoro‐Jade C and fluorescent immunohistochemistry focused on IBA‐1 microglia. RESULTS: Aged mice treated with PGJ2 exhibited spatial learning and long‐term memory deficits, as well as neurodegeneration in CA3 pyramidal neurons. Aged mice that received co‐infusions of PACAP27 exhibited remediated learning and memory performance and decreased neurodegeneration in CA3 pyramidal neurons. Moreover, microglial activation in the CA3 region was also reduced in aged mice cotreated with PACAP27. CONCLUSIONS: Our data show that PGJ2 can produce a retrograde spread of damage not observed in PGJ2‐treated young mice, leading to age‐dependent neurodegeneration of hippocampal neurons producing learning and memory deficits. PACAP27 can remediate the behavioral and neurodegenerative effects that PGJ2 produces in aged subjects. Targeting specific neurotoxic prostaglandins, such as PGJ2, offers great promise as a new therapeutic strategy downstream of cyclooxygenases, to combat the neuronal deficits induced by chronic inflammation.